Development of a 2D Laser Rangefinder Based 3D Scanning System for Wheeled Mobile Robot Applications - Gokhan BAYAR; Tugay Kadir OLGUNER (International Journal of Applied Methods in Electronics and Computers, 2016)
In this paper, a 2D laser rangefinder based 3D scanning system is proposed. The system developed is constructed using a laser scanner which has capability to scan its 240 0 surrounding in 0.35 0 resolution. The third dimension is built by designing a rotating head on which a 2D laser scanner is mounted. A DC actuator is used to rotate the rotating head. It is equipped with a high resolution quadrature encoder and a gearhead. The rotational velocity of the rotating system is determined according to the working frequency of the laser scanner. A mathematical model is developed to be able to deal with the point cloud composed of the data coming from laser scanner and encoder. The whole system is implemented in Matlab Simulink environment. The algorithm developed to create 3D shape of the objects and working environment is created to be used in real-time operations. The system proposed, experimental setup developed and the experimental results are presented in this paper in details.